2023
DOI: 10.3389/fimmu.2022.950079
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells and natural killer cells: The road to a successful oncolytic virotherapy

Abstract: Every type of cancer tissue is theoretically more vulnerable to viral infection. This natural proclivity has been harnessed as a new anti-cancer therapy by employing oncolytic viruses (OVs) to selectively infect and destroy cancer cells while providing little or no harm with no toxicity to the host. Whereas the primary oncolytic capabilities of OVs initially sparked the greatest concern, the predominant focus of research is on the association between OVs and the host immune system. Numerous OVs are potent caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 174 publications
0
12
0
Order By: Relevance
“…Although DCs can preferentially move to tumor areas, they have a relatively limited inherent capacity to destroy tumor cells. 173 , 174 However, as with other OVs, the fast generation of neutralizing antibodies poses a significant challenge to effective systemic administration. Therefore, the capacity of T cells, DCs, and peripheral blood mononuclear cells (PBMCs) as some types of CCs was evaluated, in how far they could shield reovirus and myxoma virus from systemic neutralization 41 , 42 , 94 ( Table 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although DCs can preferentially move to tumor areas, they have a relatively limited inherent capacity to destroy tumor cells. 173 , 174 However, as with other OVs, the fast generation of neutralizing antibodies poses a significant challenge to effective systemic administration. Therefore, the capacity of T cells, DCs, and peripheral blood mononuclear cells (PBMCs) as some types of CCs was evaluated, in how far they could shield reovirus and myxoma virus from systemic neutralization 41 , 42 , 94 ( Table 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…NK cells play an important role in the initial immune response and can target and kill virus-infected cells and cancer cells. It is also activated by the stimulation of cytokines and chemokines and is one of the methods that can lead to the activation of innate and adaptive immune cells ( 38 , 39 ). Our results showed that the EA-treated group had significantly increased NK cell activity.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the EA-treated group had significantly increased NK cell activity. According to a previous report, NK cells are activated by IFN- or macrophage-derived cytokines, and by recognizing changes in major histocompatibility complex (MHC) class expression and blocking the activation of non-infected cells, only infected cells selectively induce apoptosis ( 39 ). In this result, EA may play an effective role in activating NK cells to clear cells infected with viruses and bacteria and may enhance cell-mediated immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor microenvironment (TME), an intricate assembly of nonmalignant cellular entities, vascular structures, and extracellular components, plays a cardinal role in facilitating tumor progression, metastasis, and invasion [1,2]. Its immunological profile, marked by a high prevalence of tumor-associated macrophages (TAMs), has been associated with the prognosis of patients, cementing the integral role of the TAMs in the tumor milieu [3][4][5][6]. With TAMs playing diverse roles in tumor biology, understanding their composition can illuminate the complex dynamics of tumor progression, enhance predictive accuracy regarding disease outcomes, and inform the development of innovative anti-cancer strategies.…”
Section: Introductionmentioning
confidence: 99%